The Production of Fat-Containing Cultured Meat by Stacking Aligned Muscle Layers and Adipose Layers Formed From Gelatin-Soymilk Scaffold - Li, Chi-Han; Yang, I-Hsuan; Ke, Cherng-Jyh; Chi, Chih-Ying; Matahum, Jefunnie; Kuan, Che-Yung; Celikkin, Nehar; Swieszkowski, Wojciech; Lin, Feng-Huei (Frontiers in Bioengineering and Biotechnology, 2022)
Tissue engineered cultured meat has been proposed as an emerging innovative process for meat production to overcome the severe consequences of livestock farming, climate change, and an increasing global population. However, currently, cultured meat lacks organized tissue structure, possesses insufficient fat content, and incurs high production costs, which are the major ongoing challenges. In this study, a gelatin scaffold was synthesized using gelatin and soymilk to create a friendly environment for myogenesis and adipogenesis in C2C12 and 3T3-L1 cells, respectively. The fat containing cultured meat was fabricated with an aligned muscle-like layer and adipose-like layer by stacking these layers alternately. The muscle-like layer expressing myosin and the adipose-like layer abundant in fat were sandwiched to form fat containing muscle tissue. The cytotoxicity and cell survival rate were evaluated using the WST-1 assay and live/dead staining. Myogenesis was confirmed by the expression of myogenin and myosin. The myotubes, myofibrils, and sarcomeres were observed under an inverted microscope, fluorescence microscope, and scanning electron microscope. Adipogenesis was evaluated by protein expression of the peroxisome proliferator-activated receptor , and oil droplet accumulation was determined by fluorescence microscopy with Nile Red stain. Extracellular matrix secretion was examined by safranin-O staining. In this study, the cultured meat was prepared with muscle-like texture with the addition of pre-adipocyte, where the multilayered muscle-like tissues with fat content would produce juicy cultured meat.